Respuesta :

4(x + -3) + -1r + 2x = 5(3x + -7) + -9x

Reorder the terms:
4(-3 + x) + -1r + 2x = 5(3x + -7) + -9x
(-3 * 4 + x * 4) + -1r + 2x = 5(3x + -7) + -9x
(-12 + 4x) + -1r + 2x = 5(3x + -7) + -9x

Reorder the terms:

-12 + -1r + 4x + 2x = 5(3x + -7) + -9x

Combine like terms: 4x + 2x = 6x

-12 + -1r + 6x = 5(3x + -7) + -9x

Reorder the terms:

-12 + -1r + 6x = 5(-7 + 3x) + -9x
-12 + -1r + 6x = (-7 * 5 + 3x * 5) + -9x
-12 + -1r + 6x = (-35 + 15x) + -9x

Combine like terms: 15x + -9x = 6x

-12 + -1r + 6x = -35 + 6x

Add '-6x' to each side of the equation.
-12 + -1r + 6x + -6x = -35 + 6x + -6x

Combine like terms: 6x + -6x = 0

-12 + -1r + 0 = -35 + 6x + -6x
-12 + -1r = -35 + 6x + -6x

Combine like terms: 6x + -6x = 0

-12 + -1r = -35 + 0
-12 + -1r = -35

Solving

-12 + -1r = -35

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '12' to each side of the equation.

-12 + 12 + -1r = -35 + 12

Combine like terms: -12 + 12 = 0

0 + -1r = -35 + 12

-1r = -35 + 12

Combine like terms: -35 + 12 = -23

-1r = -23

Divide each side by '-1'.

r = 23

result

r = 23

ACCESS MORE